Screening and Grading of Textural Interface Opacities in DSAEK Grafts with the M-TIO Scale for Predicting Visual Outcomes - Marina S. Chatzea; George D. Kymionis; Dionysios G. Vakalopoulos; Robert C. O’Brien; Daniella Mora; Katrina Llanes; Elizabeth Fout; William Buras; Concetta Triglia; Rahul S. Tonk; Sonia H. Yoo (Diagnostics)
Background: Textural Interface Opacities (TIOs) following Descemet’s Stripping Automated Endothelial Keratoplasty (DSAEK) have become a notable postoperative concern. Several studies have attempted to identify associations between TIO development and intraoperative factors, including fluid dynamics, irregular stromal surfaces, viscoelastic usage, and recipient immunological responses. Despite these efforts, the precise etiology of TIO remains uncertain. TIO has not been considered predictable in the preoperative setting. Its detection has relied exclusively on slit-lamp biomicroscopy, a subjective approach lacking standardized diagnostic criteria, which limits diagnostic reliability and is highly susceptible to interobserver variability. Methods: Optical Coherence Tomography (OCT) images of DSAEK-processed corneal grafts, prepared using the same microkeratome and technique for transplantation at the Bascom Palmer Eye Institute, underwent blinded analysis using a newly developed grading scale termed “M-TIO”. This analysis focused on DSAEK-processed grafts OCT images to evaluate and categorize the occurrence of TIO and assess the final visual acuity of the patients at the 1-year postoperative evaluation. Results: Based on the results, the M-TIO grading scale demonstrated strong predictive value, with higher grades on OCT of DSAEK lenticules consistently associated with worse postoperative visual acuity. The study included 221 donor corneas transplanted from 2019 to 2023. Greater TIO based on the “M-TIO” grading scale was associated with worse recipient logMAR VA (Mean 0.151 [99% CI: 0.077 to 0.225] for corneas with no TIO, increased to 0.680 [99% CI: 0.532 to 0.828] for corneas with the greatest TIO grade). These findings highlight the clinical utility of the M-TIO scale as an objective and reliable preoperative tool for assessing graft quality and predicting postoperative visual outcomes. Conclusions: This study introduces the “M-TIO” grading scale, which provides a standardized and objective method for evaluating Textural Interface Opacities in DSAEK grafts prior to transplantation. Our results demonstrate a clear association between the severity of TIO as graded by the M-TIO scale, and postoperative visual outcomes, with higher TIO grades correlating with worse visual acuity, emphasizing its value in improving graft selection, and clinical decision-making in DSAEK.